Surrender, Catch, and the Imp of Fieldwork. (November 2019) - Whitaker, Emilie Morwenna; Atkinson, Paul
We build on the work of Kurt Wolff to capture some distinctive aspects of ethnographic fieldwork. Drawing on the sociology of knowledge and phenomenology, Wolff introduced and developed the idea of surrender-and-catch to encapsulate the twin processes of engagement and reflection. Although Wolff's ideas were not developed exclusively in relation to ethnography, he grounded them in his own community study. But he extended the general idea to encompass virtually any aspect of sociological or phenomenological analysis. We extend the idea to incorporate what we call the "imps" of ethnographic fieldwork. For neither surrender nor catch are themselves predictable or perfectly under the ethnographer's control. Although fieldwork is itself unpredictable, there may be many unanticipated "catches." Moreover, there is often an ethnographic "imp" that intrudes itself, questioning the very desirability or good sense of the fieldwork itself. The imps arise unbidden but can pose searching, sometimes unwelcome though ultimately productive questions. We illustrate the article from a brief fieldwork encounter with the world of studio photography.